Dreary Culture versus savage Nature: critical Perspectives of Nathaniel Hawthorne's Scarlet Letter - Kadhim Aldewan, Mushtaq Ahmed (Opción, 2019)
The objective of this paper is to propel a comprehension of Hawthorne's frame of mind towards the Culture/Nature division through rehashing The Scarlet Letter and to determine moral ideas out of nature via comparative qualitative research methods. As a result, Nature identifies itself with Hester's anguish stirring in her unconscious. It supplies ethical and moral insights into Hester's dilemma. In conclusion, HAWTHORNE’s (2000) though mostly elevates Nature as the essential embodiment of ethics, wisdom, and values, he seeks to promote a reconsidering of one's beliefs and one's vision of Nature for sound awareness and essential unity of life.